Hand collection as a method for assessing the community structure of carabid beetles - Andersen, Johan; Arneberg, Per (Pedobiologia, 2016)
[Display omitted] •Carabid abundance estimates from pitfall traps are biased by body mass.•We tested whether a method based on hand collecting is less subject to such bias.•Abundance estimates from hand collection are less size-biased.•Hand collection abundance estimates may also be entirely unbiased.•Limitations to hand collection are identified. Pitfall trapping is widely used to estimate population density in carabid beetle communities, but overestimates densities of large bodied species relative to smaller ones because large species move more around. The aim of the study was to test whether abundance estimates from hand collection (collection without area fixing and washing of the substratum) is less subject to such body size-related bias. This was addressed by comparing slopes of size-abundance relationships using data from hand collection with slopes estimated from pitfall trapping data. The material consisted of 246 carabid species and more than 63,000 individuals sampled in 11 habitat types. For epigean carnivores, size-abundance slopes based on hand collection data were significantly more negative than those based on pitfall trapping. This shows that population density estimates from hand collection is less subject to the size-related bias associated with pitfall trapping for this group. Hand collection slopes for epigean carnivores were also similar to slopes found using quadrate sampling in a habitat type where this method had been performed. They were also not different from the theoretical value of −0.75 predicted from the energetic equivalence rule in 5 of the 11 habitat types sampled. This suggests that epigean carnivore population density estimates from hand collection may indeed be unbiased regarding body size in many habitat types. Further studies are needed to clarify how extensively this applies. The analyses also show that hand collection underestimates densities of fossorial carnivores regardless of habitat type and overestimates densities of large bodied epigean carnivores in habitat types where large hiding objects are abundant. For phytophages, no significant differences were found between the performance of hand collection and pitfall trapping.